Pathway to peaceful resolution in Myanmar's Rakhine State - Lee, R; Ware, A (Refugee Studies Centre, University of Oxford, 2016)
Loud nationalistic voices and powerful vested interests stand in the way of cooperation between the Rakhine and Muslim communities and solving displacement.